The role of leadership in business model innovation: a case of an entrepreneurial firm from India - Abrar Ali Mohammadusman Saiyed (New England Journal of Entrepreneurship (NEJE), 2019)
Purpose The purpose of this paper is to explore the relationship between leadership and business model innovation (BMI) in an entrepreneurial firm. From the literature, it was found that the role of a leader in BMI was unexplored. A research framework was created which was the replication of the model created showing the relationship between leadership and innovation. Design/methodology/approach The qualitative single in-depth case study was used to understand the effects of leadership in BMI. The case of an entrepreneurial firm in the graphic and animation education sector from India was chosen to test the research framework. The leader of Xplora Design Skools was observed closely, and he was interviewed multiple times. Findings From the analysis, it was clear that, in this organization, the leader was a trigger for BMI through creating and influencing creativity and innovation in the organization. This case also shows that he was making tangible contribution to the work being done and motivating his employees. These initiatives show his influence on the process or execution of BMI. Originality/value This is the first study explores the role of a leader in BMI in an entrepreneurial firm in emerging economy contexts like India.
Keywords: 650; Leadership; Entrepreneurship; Emerging economy; Business model innovation